Terms and concepts in education studies: a comparative analysis - Palomba , Donatella (Rivista di Storia dell’Educazione, 2018)
This essays intends to make a contribution towards the theoretical and conceptual clarification called for by the “Rivista di Storia dell’educazione”, through a precise and in-depth analysis of terms and concepts employed to denote the field of comparative studies in education in the Italian context as well as in a wider international one. An in-depth work in this direction permits to avoid the risks of misunderstanding and misinterpretation, that are all the more insidious and harmful for the development of research when one moves in the international ambit. Moreover, and perhaps even more importantly, such work allows to probe and to compare the different meanings that concepts which on the face of it may seem similar, take in different cultural traditions, and it represents therefore a fundamental enrichment offered by comparison to the development of educational thinking, bringing its own original contribution to the theoretical reflection on education.